The HIV pre-exposure prophylaxis continuum of care among women who inject drugs: A systematic review - Guy, Danielle; Doran, Jason; White, Trenton M.; van Selm, Lena; Noori, Teymur; Lazarus, Jeffrey V. (Frontiers in Psychiatry, 2022)
Objective: People who inject drugs have substantial risk for HIV infection, especially women who inject drugs (WWID). HIV pre-exposure prophylaxis (PrEP), a highly-effective HIV prevention drug, is uncommonly studied among WWID, and we aimed to synthesize existing knowledge across the full PrEP continuum of care in this population. Data sources: We searched for peer-reviewed literature in three electronic databases, conference abstracts from three major HIV conferences, and grey literature from relevant sources. Study Design: Systematic Literature review. Data collection/extraction methods: Eligibility criteria included quantitative, qualitative or mixed-methods studies with primary data collection reporting a PrEP-related finding among WWID, and published in English or Spanish between 2012–2021. The initial search identified 2,809 citations, and 32 were included. Data on study characteristics and PrEP continuum of care were extracted, then data were analyzed in a narrative review. Principal Findings: Our search identified 2,809 studies; 32 met eligibility requirements. Overall, awareness, knowledge, and use of PrEP was low among WWID, although acceptability was high. Homelessness, sexual violence, unpredictability of drug use, and access to the healthcare system challenged PrEP usage and adherence. WWID were willing to share information on PrEP with other WWID, especially those at high-risk of HIV, such as sex workers. Conclusions: To improve PrEP usage and engagement in care among WWID, PrEP services could be integrated within gender-responsive harm reduction and drug treatment services. Peer-based interventions can be used to improve awareness and knowledge of PrEP within this population. Further studies are needed on transgender WWID as well as PrEP retention and adherence among all WWID.